The Relationship Between Pregnant Women's Satisfaction With Antenatal Care And The Regularity Of Antenatal Check-Ups At The Tamalanrea Health Center In Makassar. - Hadijah Hadijah; Rizky Auliah Juniarti (Sean Institute, 2023)
Pregnant women's satisfaction with ANC services is one of the factors that influence pregnant women to make repeat visits to check their pregnancy. Antenatal care is the most important component of health services to reduce maternal and infant mortality. The success of antenatal care efforts depends on health workers and the participation of pregnant women themselves. The purpose of this study was to identify pregnant women's satisfaction with ANC services and the relationship between pregnant women's satisfaction and the regularity of antenatal check-ups. The research design used was